Pengembangan Potensi Objek Wisataalam Dan Budaya Cangkuang (Studi Kasus di Desa Cangkuang Kecamatan Leles Kabupaten Garut Jawa Barat) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT: Garut Regency is a tourist destination area that has many tourism area spread over the district. One of tourism object in Garut Regency is the Cangkuang Natural and Cultural Tourism object located in Cangkuang Village, Leles district. It has an ancient temple, traditional settlement and scared grave. The objective of this study is (1) to identify tourism potential of Cangkuang Natural and Cultural Tourism Object. (2) to identity people and tourists perception (3) to identify people participation in developing tourist object and (4) to identify development indication that can be used in the future. It is used survey method by use scoring system, giving score in each research variable. Based on the result of the study on tourism potential of the Cangkuang Natural and Cultural Tourism Object and people participation, the location is directed as natural and cultural tourism s well as water tourism such has fishing, rowing and swimming. Whereas based on the tourist perception it need to be held restoration and adding facility and infrastructures that support it development efforts.